العلاقة بين التستوستيرون الكلي في البلازما والمتلازمة الاستقلابية لدى المرضى الذّكور - سلمان ربا; شريتح أحمد; منصور مهتدي (Latakia University Journal -Medical Sciences Series, 2019)
Introduction: The prevalence of metabolic syndrome (Mets) is 20-25% of adults worldwide. Hypogonadism is associated with Mets and it may be a risk factor for type 2 diabetes and cardiovascular diseases. Aim: To study Hypogonadism prevalence in male patients with Mets and study the relationship between plasma total testosterone levels(TT) and the Mets components. Materials and Methods: This is a cross-sectional study included 157 patients. Body mass index(BMI), waist circumference(WC), Blood Pressure(BP) and (TT), High density lipoprotein cholesterol(HDL-c), Triglycerides (TG) and Glucose(Glu) were assessed. Results: Prevalence of Hypogonadism was 38.6%. There was statistically significant correlation between TT and WC, BMI, Glu and decreased HDL-c. The relationships were not statistically significant between TT and TG or BP. Conclusion: It is important to screen for hypogonadism in metabolic syndrome patients مقدمة: تبلغ نسبة انتشار المتلازمة الاستقلابية في العالم بنحو بـ 20 – 25 % من البالغين. إن قصور الأقناد مرتبط بالمتلازمة الاستقلابية، وقد يكون عامل خطر لتطور الداء السكري نمط2 والأمراض القلبية الوعائية. هدف البحث: دراسة شيوع قصور الأقناد لدى مرضى المتلازمة الاستقلابيّة الذّكور ودراسة العلاقة بين مستويات التستوستيرون ومكونات المتلازمة الاستقلابية. طرائق البحث: هذه الدراسة مقطعية عرضانية شملت 157 مريضاً مصاباً بالمتلازمة الاستقلابية تم حساب مشعر كتلة الجسم (BMI)، قياس محيط الخصر (WC)، قياس الضغط الشرياني (BP) ومعايرة التستوستيرون الكلي في المصل (TT)، الشحوم الثلاثية (TG)، كوليسترول البروتين الشحمي مرتفع الكثافة (HDL-c)، سكر الدم (Glu). النتائج: بلغت نسبة انتشار قصور الأقناد 38.6 % وتبين وجود علاقة عكسية هامة بين التستوستيرون ومحيط الخصر ومشعر كتلة الجسم وسكر الدم ووجود علاقة ايجابية هامة بين مستويات التستوستيرون وكوليسترول البروتين الشحمي عالي الكثافة. لم تكن العلاقة هامة مع مستويات الشحوم الثلاثية أو الضغط الشرياني. الخلاصة: من الضروري التحري عن قصور الأقناد لدى مرضى المتلازمة الاستقلابية الذكور.